Geodetic and seismic observations of endogenous earthquakes and faulting at the Tungnakvíslarjökull landslide in south Iceland - Ylse Anna De Vries 1998- (2024)
The large 0.8 km² deep-seated landslide north of Tungnakvíslarjökull, an outlet glacier of Mýrdalsjökull on the flanks of Katla volcano, has moved at least 200 m since 1945, with an acceleration in the period from 2000 to 2010. The area surrounding Tungnakvíslarjökull has shown clustered seismic activity in the same period, but the relationship between the seismicity and landslide motion is unclear. In this thesis, pixel tracked displacement maps of landslide movement based on synthetic aperture radar TerraSAR-X satellite data, are presented spanning the period between 2010 and 2023. This thesis also studies seismic data collected between July 2020 and November 2021 using two temporary seismometers placed on the landslide. Refined locations of local earthquakes are computed using the NonLinLoc software. Additional analysis of earthquake waveforms is presented. Fifteen second interval kinematic solutions of continuous GNSS displacement from two stations (TKJS and TKJ2) on the landslide are related to the displacement maps and seismic observations. In addition to a gradual slowing of bulk landslide deformation from 8.5±4.8 m/yr in 2010 to around 1.5±2 m/yr in 2023, near-horizontal displacements show block-like structures that are interpreted to be independently moving segments bounded by faults within the landslide body. The earthquake locations point at shallow sources within the landslide body, with timings that correlate strongly with rapid dm-scale 'jerky' displacements shown from the GNSS data. A model is presented of propagating minor fault movements in the landslide during jerky movements that cause low-magnitude landslide induced, endogenous slopequakes. The landslide-local earthquakes show similarities to the previously observed long-period Goðabunga earthquakes, helping inform interpretations of this seismic cluster on Katla. Direct observation of a slopequake coinciding with a large near-instantaneous deformation within a slowly moving landslide, indicative of fracturing with in the landslide body, has ...